A live attenuated mutant of Salmonella Montevideo triggers IL-6, IFN-γ and IL-12 cytokines that co-related with humoral and cellular immune responses required for reduction of challenge bacterial load in experimental chickens. (February 2017) - Lalsiamthara, Jonathan; Lee, John Hwa
Highlights: Oral and intramuscular immunizations of chickens with live attenuated mutant of Salmonella Montevideo JOL1599. Increase productions of IgG, IL-6, IFN-γ and IL-12 in JOL1599 immunized group. Increase specific cell proliferations of circulating lymphocytes and splenic CD3+CD4+ T-lymphocytes. No conspicuous adverse reactions observed upon repeated immunizations of JOL1599. Abstract: A live attenuated Salmonella enterica serovar Montevideo (SM) mutant JOL1599 was constructed by deletion of virulence-associated genes. The protective efficacy and immune response profiles of chickens immunized with JOL1599 were investigated. Immunized chickens demonstrated significant increases in plasma IgG and lymphocyte proliferative responses ( P   ≤  0.05). Increased levels of IL-6, INF-γ, and IL-12 were also observed. Immunized birds strongly responded to infection by rapid stimulation of a CD4+ subset of T cells. Organ bacterial recovery assay revealed a significant reduction in the challenge strain among immunized birds. Multiple doses of JOL1599 enhanced the immune responses of the birds as revealed by ascending trends of the immunological profiles. These findings indicate that immunization of chickens with JOL1599 may provide protection against Salmonella Montevideo infection via induction of IL-6, INF-γ, and IL-12 protective cytokines, which in turn triggers conducive humoral and cell-mediated immune responses.